2014
DOI: 10.1377/hlthaff.2014.0136
|View full text |Cite
|
Sign up to set email alerts
|

Lessons For Providers And Hospitals From Philadelphia’s Obstetric Services Closures And Consolidations, 1997–2012

Abstract: The Affordable Care Act is triggering an increase in hospital consolidation and mergers. How other hospitals respond to these disruptions in supply could influence patient outcomes. We examined the experience of Philadelphia County, Pennsylvania (coterminous with the city of Philadelphia), where thirteen of nineteen hospital obstetric units closed between 1997 and 2012. Between October 2011 and January 2012 we interviewed twenty-three key informants from eleven hospitals (six urban and five suburban) whose obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Recruitment concluded once thematic saturation was reached. 26,27 Design Study participants were approached in the NICU within 2 weeks of the infant's anticipated discharge. After enrollment, participants completed demographics and the Parent Health Literacy Activities Test, an 8-item validated measure of health literacy and numeracy developed for families of infants.…”
Section: Participantsmentioning
confidence: 99%
“…Recruitment concluded once thematic saturation was reached. 26,27 Design Study participants were approached in the NICU within 2 weeks of the infant's anticipated discharge. After enrollment, participants completed demographics and the Parent Health Literacy Activities Test, an 8-item validated measure of health literacy and numeracy developed for families of infants.…”
Section: Participantsmentioning
confidence: 99%
“…[22][23][24] Zhang and colleagues 24 found that the closures were associated with a substantial increase in neonatal birth injuries, with increases most pronounced among mothers living in communities with closures. Allen and colleagues 25 compared time trends of iatrogenic preterm delivery, fetal growth restriction and perinatal mortality in regions of Nova Scotia, Canada, Note: CI = confidence interval, IQR = interquartile range.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, a typical SVB admission costs $15 000, compared to a cesarean admission, which cost $11 200 8,9 . These costs may be a particular concern for Medicaid which pays for 43% of the births in the United States, 10 as well as for hospitals that find that labor and delivery are a “money‐losing” service 11,12 . There is also the cost of interventions that do not improve outcomes and might decrease the chance of an SVB, such as continuous fetal heart monitoring 13 .…”
Section: Introductionmentioning
confidence: 99%